Severe signal loss in diamond beam loss monitors in high particle rate environments by charge trapping in radiation‐induced defects. Issue 10 (19th July 2016) - Kassel, Florian; Guthoff, Moritz; Dabrowski, Anne; de Boer, Wim
Abstract : The beam condition monitoring leakage (BCML) system is a beam monitoring device in the compact muon solenoid (CMS) experiment at the large hadron collider (LHC). As detectors 32 poly‐crystalline (pCVD) diamond sensors are positioned in rings around the beam pipe. Here, high particle rates occur from the colliding beams scattering particles outside the beam pipe. These particles cause defects, which act as traps for the ionization, thus reducing the charge collection efficiency (CCE). However, the loss in CCE was much more severe than expected from low rate laboratory measurements and simulations, especially in single‐crystalline (sCVD) diamonds, which have a low initial concentration of defects. After an integrated luminosity of a few fb − 1 corresponding to a few weeks of LHC operation, the CCE of the sCVD diamonds dropped by a factor of five or more and quickly approached the poor CCE of pCVD diamonds. The reason why in real experiments the CCE is much worse than in laboratory experiments is related to the ionization rate. At high particle rates the trapping rate of the ionization is so high compared with the detrapping rate, that space charge builds up. This space charge reduces locally the internal electric field, which in turn increases the trapping rate and recombination and hence reduces the CCE in a strongly non‐linear way. A diamond irradiation campaign was started to investigate the rate‐dependent electrical field deformation with respect to the radiation damage. Besides the electrical field measurements via the transient current technique (TCT), the CCE was measured. The experimental results were used to create an effective deep trap model that takes the radiation damage into account. Using this trap model, the rate‐dependent electrical field deformation and the CCE were simulated with the software SILVACO TCAD. The simulation, tuned to rate‐dependent measurements from a strong radioactive source, was able to predict the non‐linear decrease of the CCE in the harsh environment of the LHC, where the particle rate was a factor 30 higher.